2022
DOI: 10.3389/fnagi.2022.867863
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Optogenetics and Technology in Neurobiology: A Review

Abstract: Optogenetic is a technique that combines optics and genetics to control specific neurons. This technique usually uses adenoviruses that encode photosensitive protein. The adenovirus may concentrate in a specific neural region. By shining light on the target nerve region, the photosensitive protein encoded by the adenovirus is controlled. Photosensitive proteins controlled by light can selectively allow ions inside and outside the cell membrane to pass through, resulting in inhibition or activation effects. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 158 publications
1
23
0
2
Order By: Relevance
“…Recent studies have shown that a global increase in socioeconomic and medical costs has been reported for SCI; it is estimated that there are 10.4–83 million cases of SCI annually, and the disease is burdensome to patients and health management organizations [ 17 ]. Pathogenesis of SCI involves a primary mechanical injury and multiple secondary injuries induced by subsequent biological processes; among them are apoptosis, local blood flow disorders, hypoxia and ischemia of tissue, infiltration of inflammatory cells, and necrosis of nerve cells [ 18 , 19 ]. The inflammatory process contributes significantly to damage, so controlling neuroinflammation plays a crucial role in treating SCI [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a global increase in socioeconomic and medical costs has been reported for SCI; it is estimated that there are 10.4–83 million cases of SCI annually, and the disease is burdensome to patients and health management organizations [ 17 ]. Pathogenesis of SCI involves a primary mechanical injury and multiple secondary injuries induced by subsequent biological processes; among them are apoptosis, local blood flow disorders, hypoxia and ischemia of tissue, infiltration of inflammatory cells, and necrosis of nerve cells [ 18 , 19 ]. The inflammatory process contributes significantly to damage, so controlling neuroinflammation plays a crucial role in treating SCI [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of neurodegenerative diseases and tumors increases with age, there is much evidence of inverse comorbidity of these two conditions [ 1 , 2 ]. A strong correlation has been found between PCa and Alzheimer's disease (AD) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human epidermal growth factor (RhEGF) is a kind of cell growth factor composed of many kinds of amino acids, and RhEGF eye drops can effectively promote cell division and receptor binding to a certain extent, activate cells, cause cell cascade reaction, increase protein, RNA, and DNA synthesis, accelerate cell metabolism, promote the proliferation of corneal epidermal cells, and accelerate the proliferation and differentiation of corneal epithelial stem cells [ 6 ]. In addition, it can stimulate the proliferation of fibrous cells and corneal stroma and enhance the arrangement of collagen lamella [ 6 , 7 ]. Optogenetics is a technique that combines optics and genetics to control specific neurons, which is widely applied in the peripheral nervous system, such as vision study [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can stimulate the proliferation of fibrous cells and corneal stroma and enhance the arrangement of collagen lamella [ 6 , 7 ]. Optogenetics is a technique that combines optics and genetics to control specific neurons, which is widely applied in the peripheral nervous system, such as vision study [ 7 ]. The use of this drug after phacoemulsification can accelerate the regression of symptoms, shorten the recovery time of patients, and repair corneal endothelial cells and corneal injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%